ECPPM 2022 - eWork and eBusiness in architecture, engineering and construction : proceedings of the 14th European Conference on Product & Process Modelling (ECPPM 2022), 14-16 Spetember 2022, Trondheim, Norway /: proceedings of the 14th European Conference on Product & Process Modelling (ECPPM 2022), 14-16 Spetember 2022, Trondheim, Norway. (2023) - Unknown
No abstract available